A New Inflammatory Marker of Clinical and Diagnostic Importance in Diabetic Foot Infection: Systemic Immune-Inflammation Index - Balin, Safak Ozer; Ozcan, Erhan Cahit; Ugur, Kader (Sage Publications Inc, 2022)
Diabetes and associated complications still pose an important public health problem. Osteomyelitis as especially seen in patients with diabetes is associated with increased rates of morbidity and mortality. The present study aimed to investigate the clinical and diagnostic significance of inflammatory markers, including the systemic immune-inflammation index (SII) and erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and procalcitonin (PCT) to differentiate osteomyelitis and cellulitis. The present study included 96 patients with osteomyelitis (Group 1) and 151 patients with cellulitis (Group 2). Inflammatory markers were significantly elevated in Group 1 compared to Group 2 patients (p < 0.05). Furthermore, the correlation coefficients (rho) between SII and ESR, CRP, and PCT were 0.466 (p < 0.001), 0.627 (p < 0.001), and 0.501 (p < 0.001), respectively, as a result of Spearman's Rho analysis. Accordingly, a moderately positive relationship was found between the variables. The area under the curve (AUC) values for SII, ESR, CRP, and PCT in diabetic foot infection patients with osteomyelitis were 0.687, 0.722, 0.692, and 0.641, respectively. As a result of the Likelhood Ratio (LR) test, the cut-off values were 2.182 for SII (sensitivity: 39.8% and specificity: 79.8%), 76.5 mm/h for ESR (sensitivity: 59.1% and specificity: 73.1%), 109.5 mg/mL for CRP (sensitivity: 40.9% and specificity: 79.8%), and 0.44 ng/mL for PCT (sensitivity: 26.1% and specificity: 88.2%). In conclusion, given that the patients with osteomyelitis had much higher ESR, CRP, PCT, and SII levels combined with the fact that SII is a low-cost and easy-to-measure index, suggests that the same may serve as an effective and novel marker alternative to other inflammatory markers for predicting diabetic foot osteomyelitis.
Keywords: diabetic foot infections; systemic immune-inflammation index; procalcitonin; other inflammatory markers